Physicochemical comparison of commercial vs. extracted β-glucans and structural characterization after enzymatic purification - VASQUEZ MEJIA, Sandra Milena; DE FRANCISCO DE CASOS, Alicia; MANIQUE BARRETO, Pedro Luiz; MATTIONI, Bruna; ZIBETTI, André Wüst; MOLOGNONI, Luciano; DAGUER, Heitor (Vitae, 2018)
Background: β-glucans (1-3: 1-4) are soluble fibers applied to foods due to their technological properties (water binding capacity, viscosity, emulsification and stabilization) and their beneficial effects on health. The functional properties of β-glucans can be lost during the extraction and purification processes. The high viscosity of β-glucans is related to a high molecular weight and its physiological properties in the intestine. Therefore, to characterize the fiber after its extraction and purification is fundamental to understand its possible applications in foods. Objectives: characterize β-glucans extracted (EβG) and compare them with three commercial β-glucans (CβG-A, CβG-B and CβG-C) to identify its possible applications in foods and to evaluate if enzymatic purification affects molecular and structurally the β-glucans. Methods: barley β-glucans were extracted (EβG), characterized by chemical analyzes, rheological behavior, and color, and compared to three commercial β-glucans samples. Then, the extract was purified and its structural and molecular characteristics were calculated. Results: EβG contained 64.38 ± 3.54% of β-glucans, high starch contamination (12.70 ± 1.73%), high content of calcium (8894 mg/kg), pseudoplastic behavior, and dark color (L* = 52.77 ± 0.7). All commercial samples showed low starch contamination, lighter color, and Newtonian behavior. After purification starch and protein contamination decreased (0.85 ± 0.46% and 5.50 ± 0.12% respectively), increased the content of βG (69.45 ± 0.81%) and increased brightness (L* = 92.60 ± 1.70). Purified β-glucans (PβG) showed a molar weight of 690 ± 1.6 kDa and species with degree polymerization 3 (DP3) to 11 (DP11) were identified on the structure. Conclusions: EβG extracts before the purification presented a high viscosity and contamination. The enzymatic purification process was effective and allowed to maintain a high molar mass of PβG and its distinctive molecular structures (species with DP3 and DP4). The commercial samples CβG-A and CβG-B showed a low content of β-glucans. Finally, CβG-C presented the best physicochemical and rheological properties for its subsequent application in food.